Regulação coordenada da mobilização de lipídios e proteínas por hormônios, fontes de carbono e nitrogênio durante o crescimento pós-germinativo em Girassol - Galvão, Thiago Barros (2012)
The mobilization of food reserves in storage tissues and allocation of their hydrolysis products in the growing axis are critical processes for the establishment of seedlings after germination. Therefore, it is crucial for mobilization of reserves to be synchronized with the growing axis, so that photosynthetic activity can be started before depletion of reserves. For this, integrative approaches involving different reserves, different hydrolysis products and interaction between storage and growing axis tissues, either through hormones or metabolites with signaling role, can contribute greatly to the elucidation of the regulation mechanisms for reserve mobilization. In this study, was hypothesized that hormones and metabolites have different actions on reserve mobilization, and there must be a crossed effect of sugars on the mobilization of proteins and amino acids on lipids and starch mobilization in sunflower seedlings. This study was conducted with seeds of sunflower (Helianthus annuus L.) hybrid Helio 253 using in vitro culture system. Seeds were germinated on Germitest® paper and grown on agar-water 4 g/L without addition of nutrients during 9 days after imbibition (DAI) for growth curve. To verify the effect of metabolites and hormones, seedlings were transferred in the 2nd DAI to agar-water 4 g/L supplemented with increasing concentrations of sucrose or L-glutamine, abscisic acid, gibberellic acid or indolebutyric acid. The results of this study confirm that the mobilization of lipids and storage proteins occurs in a coordinated manner during post-germination growth in sunflower, corroborating the hypothesis that the application of external carbon (sucrose) and nitrogen (L-glutamine) sources can delay the mobilization of these reserves in a crossed way. Moreover, considering the changes in the patterns of reserve mobilization and partition of their products in seedlings treated with different growth regulators, it is evident that the effects of metabolites and hormones must involve, at least in part, distinct mechanisms of action